The effect of exergaming on vascular function in children - Mills, A.; Rosenberg, M.; Stratton, G.; Carter, H.; Spence, Angela; Pugh, C.; Green, D.; Naylor, L. (Mosby, Inc., 2013)
Objectives: To assess whether exergaming can induce measurable changes in heart rate (HR), energy expenditure (EE), and flow-mediated dilation (FMD) arterial function in healthy children. Study design: Fifteen children (8 males, 10.1 ± 0.7 years, body mass index 17.9 ± 2.4 kg.m−2) undertook a graded exercise test and 2 × 15 minute exergaming sessions (Xbox 360‒Kinect); high intensity exergaming (HiE, Kinect Sports–200 m Hurdles) and low intensity exergaming (LoE, Kinect Sports–Ten Pin Bowling). Brachial artery FMD, a measure of endothelial function and arterial health, was measured before and immediately after each exergaming intervention. Actihearts were used to measure EE and HR during game play and a physical activity enjoyment scale assessed enjoyment. Results: Average HR during HiE (146 ± 11 beats per minute) was greater than during LoE (104 ± 11 beats per minute, P < .05), a pattern reinforced by EE data (HiE 294.6 ± 75.2 J.min−1.kg−1, LoE 73.7 ± 44.0 J.min−1.kg−1, P < .05). FMD decreased after HiE (P < .05), whereas no change was observed following LoE. Subjects reported no differences in enjoyment between LoE and HiE. Conclusion: HiE, but not LoE, induced large HR and EE responses that were associated with effects on vascular function. This study suggests that an acute bout of HiE exergaming may provide a substrate for beneficial arterial adaptations in children.